Hubungan Mekanisme Koping Terhadap Kinerja Perawat Pelaksana Di Ruang Rawat Inap - Ardi - Septiyan; Erwin - -; Febriana - Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research  was to determine the relation ship betwen of coping mechanism and the performance of associate nurses in ward of Eka Hospital Pekanbaru.  The type of the research was correlation research with cross sectional design. Sample of this research were 63 nurses associate.The sampling technique used was total sampling. The data were analyzed by using   Chi Square test . The result of this research  showed that   p-value = 0,102 > α (0,05 and conclude  that there was no relation between  coping mechanism and performance of associate nurse in ward of Eka Hospital Pekanbaru. It is recommended that management of hospital support and educate associate nurses to enhace performance and for associate nurses to optimize  their self potential to increase performance. Keyword: Coping mechanism, performance, associate nurse